TINGKAT STRES GURU BIMBINGAN DAN KONSELING DALAM MENGHADAPI PERMASALAHAN PESERTA DIDIK DI SMA NEGERI 5 PADANG - Saputra, Agus - (Bimbingan dan Konseling, 2014)
This research was bosed of observation at SMA N 5 Padang about a teacher was stillhave a problem to encounter their students. The teacher always impatience to encountered theirstudents problems. Based on that fact, the researcher wants to know about: 1) minor stress,counselor to encounter their students problem in sman 5 padang, 2) middle stress, counselor toencounter their students problem in sman 5 padang, 3) serious stress, counselor to encountertheir students problem in sman 5 padang. This research was quantitative, a population are 8teachers counselor. Teacher as a sample this research, and the researcher use the total samplingtechnique which population as whole sample. questionnaire is an instrument which has 5 answersalternative. interval mean and percentage as data analysis. The result of the research are: 1)minor stress of the counselor are in middle level, 2) middle stress of the counselor are in middlelevel, 3) serious stress of the counselor are in middle level. The result of the research can be usefulto the counselor to increase their patience and to control their emotion and they can be aprofesional teacher. To the researcher as an information to increse his concept in his life.